Method Development and Validation of a New Stability Indicating Reverse Phase Ultra-fast Liquid Chromatographic Method for the Determination of Gefitinib (Anticancer Agent) in the Presence of an Internal Standard - Kulkarni, Dipak Chandrakant (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: A new stability indicating reverse phase ultra-fast liquid chromatographic (UFLC) method has been developed and validated for the quantification of Gefitinib in pharmaceutical formulations, that is, tablets in presence of an internal standard, Trifluridine. Gefitinib is an anticancer drug and it is used for the treatment of lung cancer, prostate cancer, and breast cancer. Materials and Methods: A mixture of tetra butyl ammonium hydrogen sulfate:methanol:Acetic acid (55:45:0.1) (pH 3.4) was used as the mobile phase for the chromatographic study (Flow rate: 0.8 mL/min; ultraviolet detection: 264 nm; Injection volume: 20 Î¼l). Shimadzu Model CBM-20A/20 Alite UFLC system with Agilent C18 column and photodiode-array detection detector was used for the present study. Results and Discussion: Gefitinib has shown linearity over the concentration range 0.5â€“100 Î¼g/ml with linear regression equation, y = 0.1027x + 0.0022 (RÂ² = 0.9999). The limit of detection and limit of quantitation were found to be 0.1392 Î¼g/ml and 0.4269 Î¼g/ml, respectively. Stress degradation studies were performed by treating Gefitinib with different stress conditions, and the method was validated as per the International Council for Harmonisation guidelines.